Resilience of Human Immuno Deficiency Virus Patients: A Concept Analysis - Eka Diana Permatasari; Untung Sujianto; Suhartini Ismail (NurseLine Journal, 2022)
The terminology of HIV resilience used in the definition is still ambiguous. These inconsistencies make it difficult to understand the findings related to resilience in HIV research. Analysis of the concept of the resilience of HIV patients is still limited in terms of its development to clarify its meaning. The purpose of this analysis is to identify the concepts of the resilience of HIV patients by identifying the attributes that determine the concept, antecedents, and consequences. The analysis of this concept uses the Walker and Avant method with eight steps of analysis. The results of the analysis reveal the resilience attributes of HIV patients, including the characteristics of individual resilience, self-competence, and social competence. The antecedents of the concept of the resilience of HIV patients are personal capacity as a source of individual resilience, interpersonal resilience resources, and spiritual strength. The consequences of the concept of HIV resilience include positive outcomes for people living with HIV in HIV care and psychological well-being. The concept of resilience in HIV patients is defined as a concept that depends on many factors that contribute positively to people living with HIV and this concept can be used for literature review for the development of futher research related to HIV resilience.